Vibration of corrugated cross-ply laminated composite plates - Khuc, Van Phu (H. : ĐHQGHN, 2017)
In the present paper the governing equations for dynamical analysis of corrugated cross-ply laminated composite plates in the form of a sin wave are developed based on the Kirchoff-Love's theory and the extension of Seydel’s technique. The problems of natural vibration and forced vibration of a plate with various boundary conditions are studied. Effects of factors as geometry dimensions, order of laminate as well as waved-amplitude on frequency of natural vibration, amplitude of forced vibration of the corrugated cross-ply laminated composite plates are also analysed.